2009
DOI: 10.1111/j.1750-8606.2008.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Curriculum‐Based Sex and STD/HIV Education Programs for Adolescents

Abstract: ABSTRACT— High rates of teen pregnancy and sexually transmitted disease (STD) are important problems in the United States. Curriculum‐based sex and STD/HIV education programs have been proffered as a partial solution. This article reviews evaluations of the impact of such programs that met specified criteria and finds that about two thirds of programs had a significant impact on behavior. The proportion having a negative impact was less than expected by chance. Those having a positive impact had such effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 47 publications
2
99
0
2
Order By: Relevance
“…65 The recent 3% increase in teen births could be a "blip," or it could be attributable to an increase in abstinence-only sex education and the concomitant reduction in accurate information about contraception. [66][67][68] Eight peer-reviewed, controlled clinical trials have revealed that giving teenagers freer access to condoms does not increase their sexual activity or encourage virginal teenagers to begin having sex, but it does increase the use of condoms among those who are already sexually active. [69][70][71][72][73][74][75][76] Advertising condoms, birth control pills, and emergency contraception on TV and radio could further decrease the teen pregnancy rate.…”
Section: Contraceptive Advertisingmentioning
confidence: 99%
See 1 more Smart Citation
“…65 The recent 3% increase in teen births could be a "blip," or it could be attributable to an increase in abstinence-only sex education and the concomitant reduction in accurate information about contraception. [66][67][68] Eight peer-reviewed, controlled clinical trials have revealed that giving teenagers freer access to condoms does not increase their sexual activity or encourage virginal teenagers to begin having sex, but it does increase the use of condoms among those who are already sexually active. [69][70][71][72][73][74][75][76] Advertising condoms, birth control pills, and emergency contraception on TV and radio could further decrease the teen pregnancy rate.…”
Section: Contraceptive Advertisingmentioning
confidence: 99%
“…90,91 Federal money should be spent on comprehensive sex education programs but not on abstinence-only programs, which have been found to be ineffective. 35,[65][66][67][68][92][93][94] 5. Pediatricians should urge the broadcast industry to air advertisements for birth control products.…”
Section: Positive Impactmentioning
confidence: 99%
“…Non seulement l'information qu'elle dispense est souvent incorrecte (Waxman, 2004), mais elle omet une grande partie de l'information dont les jeunes ont besoin pour assurer leur santé sexuelle et reproductive (Santelli et al, 2006 : 78). Les études disponibles semblent toutes indiquer qu'il est préférable de parler à la fois d'abstinence et d'autres méthodes de prévention (Kirby et Laris, 2009 ;Kirby et al, 2007).…”
Section: L'abstinence Aux éTats-unisunclassified
“…Dans les faits, la plupart des adultes rencontrés en 2008 ne voulaient pas de tels programmes, ou du moins ne voulaient pas avoir à les mettre en oeuvre, de près ou de loin. Comme on l'a noté, les données disponibles permettent de savoir assez bien quel type d'intervention « fonctionne » auprès des jeunes (Kirby, 2006(Kirby, , 2008Kirby et Laris, 2009 ;Robinson et al, 2002). Toutefois, les programmes requièrent une franche discussion de la sexualité et une approche positive qui vont à l'encontre d'une grande partie de la culture sexuelle malawite ; et d'autre part, ils doivent inclure l'information sur les contraceptifs et les préservatifs, ce qui va à l'encontre de ce qui y est religieusement acceptable.…”
Section: Le Relativisme Jette L'épongeunclassified
“…In these policies, there has been strong support for use of best practice sex education curricula based firmly in health behavior theory (Brindis, Sattley, & Mamo, 2005;Kirby & Laris, 2009). Social learning theory (Rotter, 1954), social cognitive theory (Bandura, 1991), and self-efficacy theory (Bandura, 1977), provide the theoretical foundation for the majority of evidence-based adolescent sex education programs (Kirby, Laris, & Rolleri, 2007).…”
Section: Using Evidence To Drive Sex Education Policy and Practicementioning
confidence: 99%